Millennial-scale evolution of elemental ratios in bulk sediments from the western Philippine Sea and implications for chemical weathering in Luzon since the Last Glacial Maximum. (1st August 2019) - Xiong, Zhifang; Li, Tiegang; Jiang, Fuqing; Chang, Fengming; Chen, Shuangxi
Graphical abstract: Highlights: Lower Ti-normalized element ratios indicate higher weathering intensity in Luzon. Sediment remobilization explains strong weathering of shelf sediments during the Last Glacial Maximum. Precipitation caused rapid changes in weathering intensity during the last deglaciation. Sediment weathering was probably stronger in tropical West Pacific during colder intervals of the middle–late Quaternary. Abstract: To reconstruct the chemical weathering history in Luzon, Philippines, since the Last Glacial Maximum (LGM), major and trace elements (Ti, Al, Fe, K, Ba, Rb, V, Sc, Cr, and Th) and grain size were determined for core MD06-3054 as well as the bulk and detrital fractions of three core-top samples from the western Philippine Sea (WPS). In combination with previously published Sr-Nd isotopes, our new results indicate that Ti-normalized elemental ratios in the study samples were not controlled by the quantity of biogenic, authigenic, or diagenetic materials, sediment provenance, or grain size. Instead, variations in Ti-normalized elemental ratios mainly reflect changes in chemical weathering intensity, with lower values representing stronger chemical weathering in Luzon. To assess long-term integrated chemical weathering patterns, we defined a stacked chemical weathering index (SCWI) based on all elemental ratios in the study core. Downcore SCWI records indicate that sediments deposited during the LGM underwent a degree of chemical weathering equal to that during the Holocene, and sediments deposited during the last deglaciation exhibit rapid changes in chemical weathering, with higher intensity during the Heinrich event 1 (H1) and Younger Dryas (YD), and lower intensity during the Bølling-Allerød (B/A) in the WPS. These observations are in excellent agreement with chemical weathering proxies, such as the K/Al ratios and chemical index of alteration when applied to the same core. We infer that persistent sea-level lowstand and induced reworking of poorly consolidated sediments on the eastern Luzon continental shelf during the LGM accounted for equal or slightly stronger chemical weathering for the LGM sediments relative to the Holocene sediments. Rainfall, rather than air temperature, in Luzon was responsible for the rapid changes in chemical weathering during the last deglaciation, with higher precipitation generating stronger chemical weathering during the H1 and YD than during the B/A. Our observations, combined with existing data, suggest that strong weathering of marine sediments during colder intervals of the middle–late Quaternary is likely to be a general feature of the tropical West Pacific, although the mechanism that underlies this phenomenon remains controversial.